2000
DOI: 10.1074/jbc.m003616200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucose-6-phosphatase Gene Expression by Protein Kinase Bα and the Forkhead Transcription Factor FKHR

Abstract: Glucose-6-phosphatase plays an important role in the regulation of hepatic glucose production, and insulin suppresses glucose-6-phosphatase gene expression. Recent studies indicate that protein kinase B and Forkhead proteins contribute to insulin-regulated gene expression in the liver. Here, we examined the role of protein kinase B and Forkhead proteins in mediating effects of insulin on glucose-6-phosphatase promoter activity. Transient transfection studies with reporter gene constructs demonstrate that insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
112
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(117 citation statements)
references
References 38 publications
(90 reference statements)
5
112
0
Order By: Relevance
“…IRSs Does Not-Results from a number of studies suggest that, when overexpressed, FKHR can mediate insulin repression of IGFBP-1 and G6Pase gene transcription through their PEPCK-like IRS motifs (32,34,38,60). In addition, we have previously shown that recombinant FKHR can bind an oligonucleotide representing the wild-type G6Pase region B sequence, but not an oligonucleotide containing point mutations in each of the three region B IRS motifs ( Fig.…”
Section: Disruption Of the Igfbp-1 Irss Results In A Significant Decrmentioning
confidence: 99%
See 2 more Smart Citations
“…IRSs Does Not-Results from a number of studies suggest that, when overexpressed, FKHR can mediate insulin repression of IGFBP-1 and G6Pase gene transcription through their PEPCK-like IRS motifs (32,34,38,60). In addition, we have previously shown that recombinant FKHR can bind an oligonucleotide representing the wild-type G6Pase region B sequence, but not an oligonucleotide containing point mutations in each of the three region B IRS motifs ( Fig.…”
Section: Disruption Of the Igfbp-1 Irss Results In A Significant Decrmentioning
confidence: 99%
“…Subsequently, it was shown that FKHR can bind the PEPCK, IGFBP-1, and G6Pase IRSs in vitro (16,(32)(33)(34). In addition, FKHR was shown to stimulate PEPCK, IGFBP-1, and G6Pase fusion gene expression (32,34,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that the phosphorylation status of Foxo1 might also regulate transcriptional activation properties in addition to regulating cytolocalization (24). Insulin-induced inactivation of Foxo1 appears to be one of the mechanisms through which insulin suppresses gluconeogenic gene expression as phosphoenolpyruvate carboxykinase and glucose-6-phosphatase, two enzymes involved in gluconeogenesis, are encoded by Foxo1 target genes (25,26). While regulation of phosphoenolpyruvate carboxykinase via this mechanism is controversial, recent evidence from Foxo1Ϯ mice supports such a mechanism for regulation of glucose-6-phosphatase (27).…”
mentioning
confidence: 99%
“…The cAMP analogue dibutyryl cAMP (bucladesine, db‐cAMP), a cell‐permeable stabilized cAMP mimic that also inhibits phosphodiesterase (PDE) activity, is commonly used 6, 7. Treatment of cells with db‐cAMP causes a significant stimulation of PEPCK and G6‐Pase expression, which is inhibited by the addition of insulin in a dose‐dependent manner 8, 9, 10. 8‐(4‐chlorophenylthio)cAMP (8CPT‐cAMP), like db‐cAMP, is a membrane‐permeable cAMP analogue that stimulates PEPCK and G‐6‐Pase 4, 11.…”
Section: Introductionmentioning
confidence: 99%